Results 1 to 3 of 3

Thread: Geometric Progression

  1. #1
    Newbie
    Joined
    Jan 2009
    Posts
    17

    Geometric Progression

    A geometric series has first term 1 and the common ratio r is positive. The sum of the first 5 terms is twice the sum of the terms from the 6th to the 15th inclusive. Prove that r^5 = 1/2 (sqrt3 - 1).

    I manage to get up to 2(r^5 - 1) = r^15 - r^5.

    Please help.
    Follow Math Help Forum on Facebook and Google+

  2. #2
    Junior Member AlvinCY's Avatar
    Joined
    Feb 2007
    From
    I live in Sydney, Australia.
    Posts
    69
    Quote Originally Posted by azuki View Post
    A geometric series has first term 1 and the common ratio r is positive. The sum of the first 5 terms is twice the sum of the terms from the 6th to the 15th inclusive. Prove that r^5 = 1/2 (sqrt3 - 1).



    I manage to get up to 2(r^5 - 1) = r^15 - r^5.



    Please help.
    Sum of a geometric series: $\displaystyle S_n=\frac{a(r^n-1)}{r-1}$

    $\displaystyle S_5=\frac{a(r^5-1)}{r-1}$

    $\displaystyle S_{15}=\frac{a(r^{15}-1)}{r-1}$

    The sum of the first 5 terms is twice the sum of the terms from the 6th to the 15th inclusive implies:

    $\displaystyle S_5 = 2S_{15} - 2S_5$

    $\displaystyle 3S_5 = 2S_{15}$

    $\displaystyle \frac{3a(r^5-1)}{r-1}=\frac{2a(r^{15}-1)}{r-1}$

    $\displaystyle 3a(r^5-1)=2a(r^{15}-1)$

    $\displaystyle 3(r^5-1)=2(r^{15}-1)$

    $\displaystyle 3(r^5-1)=2[(r^5)^3-1]$ (note: the expression in the brackets is now a difference of two CUBES, so we can use: $\displaystyle a^3-b^3=(a-b)(a^2+ab+b^2)$

    So $\displaystyle (r^5)^3-1=(r^5-1)(r^{10}+r^5+1)$

    $\displaystyle 3(r^5-1)=2(r^5-1)(r^{10}+r^5+1)$

    $\displaystyle 3=2(r^{10}+r^5+1)$

    $\displaystyle \frac{3}{2}=r^{10}+r^5+1$

    $\displaystyle 0=r^{10}+r^5-\frac{1}{2}$

    $\displaystyle 0=2r^{10}+2r^5-1$

    $\displaystyle 0=2(r^5)^2+2r^5-1$

    Let $\displaystyle X=r^5$

    $\displaystyle 0=2X^2+2X-1$

    Using the quadratic formula ($\displaystyle x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$),

    $\displaystyle X=\frac{-2\pm\sqrt{4-4\times2\times-1}}{4}$

    $\displaystyle X=\frac{-2\pm\sqrt{12}}{4}$

    $\displaystyle X=\frac{-2\pm2\sqrt{3}}{4}$

    $\displaystyle X=\frac{-1\pm\sqrt{3}}{2}$

    Putting $\displaystyle X=r^5$ back in:

    $\displaystyle r^5=\frac{-1\pm\sqrt{3}}{2}$

    But the question said that $\displaystyle r$ is a positive number, so $\displaystyle r^5$ must ALSO be positive, therefore $\displaystyle r^5=\frac{-1+\sqrt{3}}{2}$

    Proving that $\displaystyle r^5=\frac{1}{2}(\sqrt{3}-1)$
    Last edited by mr fantastic; Jan 20th 2009 at 02:22 AM. Reason: Added quote tags
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Newbie
    Joined
    Jan 2009
    Posts
    17
    Why sum of the first 5 terms is twice the sum of the terms from the 6th to the 15th inclusive implies:

    S_5 = 2S_15 – 2S_5
    Last edited by azuki; Jan 20th 2009 at 05:50 AM.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Geometric progression
    Posted in the Math Topics Forum
    Replies: 3
    Last Post: Apr 11th 2011, 05:06 AM
  2. Geometric Progression
    Posted in the Algebra Forum
    Replies: 4
    Last Post: Mar 17th 2010, 04:08 AM
  3. Geometric progression
    Posted in the Pre-Calculus Forum
    Replies: 1
    Last Post: Jan 12th 2010, 04:22 AM
  4. Geometric Progression or Geometric Series
    Posted in the Math Topics Forum
    Replies: 8
    Last Post: Oct 8th 2009, 07:31 AM
  5. Replies: 8
    Last Post: Mar 23rd 2009, 07:26 AM

Search Tags


/mathhelpforum @mathhelpforum